2008
DOI: 10.1038/emboj.2008.235
|View full text |Cite
|
Sign up to set email alerts
|

Molecular basis for G-actin binding to RPEL motifs from the serum response factor coactivator MAL

Abstract: Serum response factor transcriptional activity is controlled through interactions with regulatory cofactors such as the coactivator MAL/MRTF-A (myocardin-related transcription factor A). MAL is itself regulated in vivo by changes in cellular actin dynamics, which alter its interaction with G-actin. The G-actin-sensing mechanism of MAL/MRTF-A resides in its N-terminal domain, which consists of three tandem RPEL repeats. We describe the first molecular insights into RPEL function obtained … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
132
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 95 publications
(137 citation statements)
references
References 46 publications
5
132
0
Order By: Relevance
“…This raises the idea that maybe these two pathways are differentially sensitive to changes in actin monomer levels. Binding of actin to the RPEL domain is quite complex, which is highlighted by the fact that structural studies with MRTF-A have revealed complexes with either three or five actin monomers (Mouilleron et al, 2008;Mouilleron et al, 2011). Moreover, the actual MRTF-A-actin configuration in cells as well as the functional properties of the complexes with different actin stoichiometrics remain unclear.…”
Section: Discussionmentioning
confidence: 99%
“…This raises the idea that maybe these two pathways are differentially sensitive to changes in actin monomer levels. Binding of actin to the RPEL domain is quite complex, which is highlighted by the fact that structural studies with MRTF-A have revealed complexes with either three or five actin monomers (Mouilleron et al, 2008;Mouilleron et al, 2011). Moreover, the actual MRTF-A-actin configuration in cells as well as the functional properties of the complexes with different actin stoichiometrics remain unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Upon dissociation from G-actin, MAL/MRTF-A upregulates a Rhofamily dependent, but MAPK-independent, subset of SRF target genes (Gineitis and Treisman, 2001;Vartiainen et al, 2007). These genes and their promoters respond differentially to actin binding drugs: treatment with cytochalasin D activates transcription by releasing MAL from G-actin, whereas latrunculin B stabilises the G-actin-MAL complex and inhibits gene expression (Posern et al, 2002;Posern et al, 2004;Vartiainen et al, 2007;Mouilleron et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Serum-induced gene expression is directly controlled by monomeric G-actin, which forms a repressive complex with MRTFs (Posern et al, 2002;Miralles et al, 2003;Posern et al, 2004;Vartiainen et al, 2007;Mouilleron et al, 2008). Upon dissociation from G-actin, MAL/MRTF-A upregulates a Rhofamily dependent, but MAPK-independent, subset of SRF target genes (Gineitis and Treisman, 2001;Vartiainen et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Perhaps the best understood of these functions is the role of G-actin in control of nucleocytoplasmic shuttling and transcriptional activation by the MRTF family of SRF transcriptional coactivators (Miralles et al, 2003;Vartiainen et al, 2007). Signal-induced changes in the availability of Gactin regulate the assembly of different G-actin complexes on the MRTF regulatory domain, which contains three G-actin binding RPEL motifs (Mouilleron et al, 2008;Hirano and Matsuura, 2011;Mouilleron et al, 2011).…”
Section: Introductionmentioning
confidence: 99%